F
fly999999999
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
1. $\sqrt{x}(9^{\sqrt{x^2-3}}-3^{\sqrt{x^2-3}}) = 3^{2\sqrt{x^2-3}+1}-3^{\sqrt{x^2-3}+9}+6\sqrt{x}-18$
2. $2^{2x^2}+2^{2x^2+2x-1}=2^{4x-1}$
3. $4^{x-\sqrt{x^2-5}}-12.2^{x-1-\sqrt{x^2-5}}+8=0$
4. $3.25^{x-2}+(3x-10).5^{x-2}+3-x=0$
5. $log_{1-2x^2}x =\dfrac{1}{4}-\dfrac{3}{log_2(1-2x^2)^4}$
Bạn chú ý cách soạn latex, mình sửa cho bạn lần này thôi nhé
2. $2^{2x^2}+2^{2x^2+2x-1}=2^{4x-1}$
3. $4^{x-\sqrt{x^2-5}}-12.2^{x-1-\sqrt{x^2-5}}+8=0$
4. $3.25^{x-2}+(3x-10).5^{x-2}+3-x=0$
5. $log_{1-2x^2}x =\dfrac{1}{4}-\dfrac{3}{log_2(1-2x^2)^4}$
Bạn chú ý cách soạn latex, mình sửa cho bạn lần này thôi nhé
Last edited by a moderator: